The impact of socioeconomic status on survival in stage III colon cancer patients: A retrospective cohort study using the SEER census‐tract dataset. (30th June 2021) - Dhahri, Amina; Kaplan, Jori; Naqvi, Syeda M. H.; Brownstein, Naomi C.; Ntiri, Shana O.; Imanirad, Iman; Felder, Seth I.; Dineen, Sean P.; Sanchez, Julian; Dessureault, Sophie; Carballido, Estrella; Powers, Benjamin D.
Abstract: Background: The impact of socioeconomic status (SES) has been described for screening and accessing treatment for colon cancer. However, little is known about the "downstream" effect in patients who receive guideline‐concordant treatment. This study assessed the impact of SES on cancer‐specific survival (CSS) and overall survival (OS) for stage III colon cancer patients. Methods: The SEER Census Tract‐Level SES Dataset from 2004 to 2015 was used to identify stage III colon adenocarcinoma patients who received curative‐intent surgery and adjuvant chemotherapy. The predictor variable was census tract SES. SES was analyzed as quintiles. The outcome variables were OR and CSS. Statistical analysis included chi square tests for association, Kaplan–Meier, Cox, Fine and Gray regression for survival analysis. Results: In total, 27, 222 patients met inclusion criteria. Lower SES was associated with younger age, Black or Hispanic race/ethnicity, Medicaid/uninsured, higher T stage, and lower grade tumors. CSS at the 25th percentile was 54 months for the lowest SES quintile and 80 for the highest. Median OS was 113 months for the lowest SES quintile and not reached for highest. The 5‐year CSS rate was 72.4% for the lowest SES quintile compared to 78.9% in the highest ( p  < 0.001). The 5‐year OS rate was 66.5% for the lowest SES quintile and 74.6% in the highest ( p  < 0.001). Conclusion: This is the first study to evaluate CSS and OS in an incidence‐based cohort of stage III colon cancer patients using a granular, standardized measure of SES. Despite receipt of guideline‐based treatment, SES was associated with disparities in CSS and OS. Abstract : This is the first study to evaluate CSS and OS in a national cohort of stage III colon cancer patients using a granular, standardized measure of SES. We showed that despite receipt of guideline‐based treatment, socioeconomic status is associated with disparities in overall and cancer specific survival. These findings suggest opportunities to improve colon cancer outcomes farther down the cancer care continuum.